Sistem Informasi Layanan Kegiatan Anggota Pemberdayaan Kesejahteraan Keluarga (PKK) - Alfonsa Maria Bili; Adelbertus Umbu Janga; Mitra Permata Ayu (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The Family Welfare Empowerment (PKK) is a community organization that plays a strategic role in improving the quality of family life through various programs covering education, health, economy, and social aspects. However, in practice, the recording and management of member data as well as PKK activities are still carried out manually. This condition creates several challenges, including difficulties in archiving, limited access to information retrieval, and delays in preparing reports required by administrators and stakeholders. This study aims to design and develop a web-based information system for PKK member activity services that can manage member data, record activities, track attendance, and generate reports quickly, accurately, and efficiently. The system development method employed an object-oriented approach, consisting of requirement analysis, system design, implementation, and testing stages. The implementation results show that the developed information system can improve organizational service efficiency, assist administrators in monitoring member activeness, and reduce potential errors in data recording. Furthermore, the system provides better support for data-driven decision-making, thereby enabling PKK to become more modern, transparent, and adaptive to technological developments. Thus, this system has the potential to serve as an innovative solution to sustainably enhance the performance of PKK organizations.